Formulation and Evaluation of Sunscreen Body Butter Preparation Containing Soursop Leaf Extract (Annona muricata L.) and Its Influence on Sun Protection Factor (SPF) Value - Noor Kholilah; Lathvi Masyithah; Dona Suzana (JSFK (Jurnal Sains Farmasi & Klinis), 2025)
The leaf part of the soursop plant (Annona muricata L.) contains phenolic compounds, especially flavonoids and tannins, which have sunscreen potential due to the presence of chromophore groups. These groups have conjugated double bonds capable of absorbing ultraviolet rays, thus reducing their intensity on the skin. This study aims to formulate sunscreen body butter preparations from soursop leaf extract with good stability and to determine the effect of varying concentrations of soursop leaf extract on the SPF value of the preparations. Soursop leaf ethanol extract was obtained by maceration with 70% ethanol. Body butter was formulated due to its efficacy in preserving skin hydration, improving softness, and protecting against environmental stressors. SPF value measurements were conducted using spectrophotometric methods. The evaluation results of sunscreen body butter from formulas 1, 2, and 3 were sequentially light green, strong green, and dark green in color; with a typical weak extract odor, homogeneous, pH 7, and a spreadability of 6 - 6.5 cm. Stability testing with a cycling test showed that all three preparation formulas were stable. The SPF values of sunscreen body butter containing ethanol extract of soursop leaves for F1 extract 1% were 7.07, categorized as extra protection; F2 extract 2% was 10.51, categorized as maximum protection; and F3 extract 3% was categorized as ultra protection. The higher the concentration of extract in the preparation, the higher the SPF value it possesses